Program Corporate Social Responsibility di Industri Hotel: Sebuah Keuntungan atau Kerugian untuk Hotel - Maria Pia Adiati (Binus Business Review, 2012)
A word of CSR which stands for Corporate Social Responsibility is now becoming popular and more often many companies insert the CSR activities into its company profile. CSR has another different names such as Social Activity or Sustainability Development. CSR program according to wikipedia ia an organization or company has a responsibility to its customer, employees, share holders, community and environment in every aspect involved in company operasional. In the management science, there is a level whereas it is called social responsibility or it is just social obligation. Many opinions argues that CSR program will reduce the profit of the respected company. But many opinions denies the previous argue by saying the CSR program is a long term program profit gain since the short term result is good public image. The good public image will lead the loyalti of customer to keep using the product or service from the hotel. The customer loyalti also affected by the customer’s opinion, if they involves in the social activities held by the hotel, they also participate in a social activity.